2010
DOI: 10.1007/s11356-010-0293-3
|View full text |Cite
|
Sign up to set email alerts
|

The state of indoor air quality in Pakistan—a review

Abstract: Indoor air pollution has a significant impact on the health of the population in Pakistan. The use of biomass fuel as an energy source is the biggest contributor to poor indoor air quality followed by smoking. In order to arrest the increasing levels of indoor pollution, there is a dire need to recognize it as a major health hazard and formulate a national policy to combat it. An integrated effort, with involvement of all stakeholders, could yield promising results. A countrywide public awareness campaign, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Indoor aerosol size and composition largely depend on the in-situ emission source, such as cooking, cleaning, or heating (Wallace, 1996;Hussein et al, 2006;Colbeck et al, 2010;Hsu et al, 2012). However, when indoor sources are absent, indoor aerosol concentrations correlate strongly to those outdoors .…”
Section: Introductionmentioning
confidence: 99%
“…Indoor aerosol size and composition largely depend on the in-situ emission source, such as cooking, cleaning, or heating (Wallace, 1996;Hussein et al, 2006;Colbeck et al, 2010;Hsu et al, 2012). However, when indoor sources are absent, indoor aerosol concentrations correlate strongly to those outdoors .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that concentrations of pollutants in the indoor environment are often higher than those typically encountered outdoors, while the estimated risk to human health from indoor sources is about 1000 times higher than the one resulting from exposure to outdoor pollutants (Colbeck et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…The likely reason is the better cooking efficiency of wood in comparison to dung and crop residue. Stove at waist height reduces direct exposure of cook leaning over fire (0,90,10) 3.4 Awareness and use of methods to reduce exposure to biomass fuel smoke A vast majority (87%) was aware of some methods to reduce indoor air pollution exposure. Their awareness was matched against the intervention methods mentioned previously -i.e., changing the source of pollution, improvement in the cooking environment and modifying the user behaviour ( Table 4).…”
Section: Awareness Of Health Impacts Of Cooking Fuelsmentioning
confidence: 99%
“…According to the Pakistan Strategic Country Environmental Assessment by the World Bank [9], indoor air pollution accounts for 28,000 deaths per year and 40 million cases of acute respiratory illness. Despite the mounting evidence that indoor pollution poses a significant health impact, the problem has received relatively little attention from government and academics and studies on levels of indoor air pollution in Pakistani households are scant [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation